2006
DOI: 10.1055/s-2006-942373
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Terminal Conjugated Enynes: Cu-Mediated Cross-Coupling Reaction of Alkenyldialkylborane with (Trimethylsilyl)ethynyl Bromide

Abstract: The cross-coupling reaction of (E)-and (Z)-alk-1-enyldialkylborane with (trimethylsilyl)ethynyl bromide proceeds in the presence of a catalytic amount of copper(II) acetylacetonate and a base under extremely mild conditions to provide conjugated enynes with a distal carbon-carbon triple bond. Employing sodium methoxide (1 M) as the base results in not only cross-coupling but also desilylation affording both (E)-and (Z)-alk-3-en-1-ynes, exclusively, while lithium hydroxide monohydrate gives both (E)-and (Z)-1-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…While instances of Cu-based Suzuki coupling have appeared in the literature, 136 , 137 these catalysts tend to employ bidentate acetylacetone (acac) or acetate/triflate ligands. 138 , 139 Thus, it is interesting to note that each of the thermodynamically most appealing Cu catalysts involves either a tris(dimethylamino)phosphine or bulky N-heterocyclic carbene ( Fig. 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…While instances of Cu-based Suzuki coupling have appeared in the literature, 136 , 137 these catalysts tend to employ bidentate acetylacetone (acac) or acetate/triflate ligands. 138 , 139 Thus, it is interesting to note that each of the thermodynamically most appealing Cu catalysts involves either a tris(dimethylamino)phosphine or bulky N-heterocyclic carbene ( Fig. 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the terminal conjugated enyne is a useful building block for the synthesis of natural products in organic synthesis, because the terminal conjugated enyne unit occurs in natural products such as laurencin [16], dactylyne [17], quinolizidine [18], and histrionicotoxin [19]. Very recently, Hoshi et al reported the synthesis of terminal conjugated enynes via Cu-mediated Suzuki-Miyaura cross-coupling reaction of alkenyldialkylboranes with (trimethylsilyl)ethynyl bromide [20]. Our methodology involves the preparation and the reactions of the building block (Z)-3-(tributylstannyl)-alk-3-en-1-ynes 3 which can be conveniently obtained according to Scheme 1: Sonogashira coupling of alkenyl iodides with terminal alkynes provides a simple and general route for the synthesis of conjugated enynes [21].…”
Section: Resultsmentioning
confidence: 99%
“…[10] TheSuzuki-Miyaura reaction could potentially be used to transform boronic esters into alkynes in conjunction with an alkynyl halide.However,the use of chiral boronic acids/esters in such cross-coupling reactions is not known;t he only reported examples are those that utilize primary sp 3 -, sp 2 -, and sp-type boron species,w hich are compounds that undergo facile transmetalation. [11,12] Another attractive method involves electrophile-induced 1,2-migration of an alkynyl boronate followed by deboronation (Scheme 1A). However, this approach is only applicable to symmetric trialkylboranes (BR 3 ) [13,14] and borinic esters (BR 2 OR), [15] which suffer from an umber of drawbacks,i ncluding difficulty in preparing an enantioenriched form, poor stability,a nd the poor atom economy of subsequent transformations (two Rg roups are wasted in borane transformations).…”
mentioning
confidence: 99%